Effects of paclitaxel and methotrexate associated with cholesterol-rich nanoemulsions on ischemia-reperfusion injury after unilateral lung transplantation in rats - Angela da Silva Battochio; Elaine Rufo Tavares; Aristides Tadeu Correia; Francine Maria de Almeida; Priscila Oliveira Carvalho; Maria Carolina Guido; Paulo Manuel Pêgo-Fernandes; Raul Cavalcante Maranhão; Rogerio Pazetti (Scientific Reports)
Abstract Currently, the barrier to successful lung transplantation is ischemia and reperfusion injury, which can lead to the development of bronchiolitis obliterans. Paclitaxel and methotrexate are drugs known to inhibit cell proliferation and have anti-inflammatory effects, and the association of these drugs with cholesterol-rich nanoparticles has been shown to be beneficial in the treatment of other transplanted organs. Thirty-three male Sprague Dawley rats were divided into 3 groups: Basal group, no intervention; Control group, received only nanoparticles; Drug group, paclitaxel and methotrexate treatment. Donors and recipients were treated with nanoparticle-paclitaxel and nanoparticle-methotrexate, respectively, 24 h before surgery. The donor lungs from the Drug group were perfused with a preservation solution supplemented with nanoparticles-paclitaxel. After 12 h, the left lung was implanted and reperfused for 1 h. Recipients had an increase in erythrocytes, neutrophils and hemoglobin and a decrease in lymphocytes, and an increase in oxygenation and lactate and a decrease in carbon dioxide. These animals showed an increase in urea and creatinine. The grafts showed perivascular edema and hemorrhage, as well as elevated values of airway resistance, tissue resistance and tissue elastance under mechanical ventilation. The tested drugs were not effective in attenuating the effects of ischemia and reperfusion injury.